Modelling of combined sewer overflow impacts on the receiving water quality: case studies Hron and Drava - Sokáč, Marek; Jerković, Marta (International Conference “Environmental Engineering”, 2017)
Paper analyses the influences of combined sewer overflows (CSO’s), on the receiving water quality, but generally deals also with various types of storm water management in urban areas. The first case study analyses the impacts of the continuous (wastewater treatment plant in the town Osijek) and discontinuous pollution sources (CSO’s in the town Osijek) on the quality of the receiving water – the Drava river (Croatia). The second modelling case study was performed on the river Hron (Slovak republic). In this study, the impacts on the water quality from combined sewer overflows form the biggest town on Hron River – Banská Bystrica were studied, as well as four feasible alternatives of storm sewer management (different mixing ratio, different size of storm tanks) were analysed. For both case studies, the mathematical simulation model MIKE11 (Danish Hydraulic Institute, DHI) was used.